SIMILARITIES AND DIFFERENCES OF TAXATION OF LEGAL AND INDIVIDUALS (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2026)
This article examines the similarities and differences in the taxation of legal entities and individuals. It explores the fundamental principles of taxation that apply to both groups, including the purpose of tax collection, compliance requirements, and the impact of tax policies on economic behavior. The article also highlights key distinctions, such as tax rates, deductions, exemptions, and reporting obligations. By analyzing these aspects, the article aims to provide a comprehensive understanding of how taxation frameworks operate for both legal and individual taxpayers.